The effect of temperature and inducer concentration on the expression of recombinant phospholipase A2 in bacterial expression system / Suhaidah Mohd Jofrry - Mohd Jofrry, Suhaidah (2009)
Phospholipase A2 is an enzyme that catalyzed the hydrolysis of long chain triglycerides producing lysophospholipids and free fatty acids. Its catalytic properties which act as powerful emulsifier causes it to be widely used in various industrial application including foods, cosmetics as well as pharmaceuticals industry. Unfortunately, most of the enzyme currently used by the manufacturer is derived from porcine which is forbidden to be consumed by Muslims. Therefore this project was aimed to produce phospholipase A2 enzyme in E. coli using recombinant technology as well as to determine the optimum incubation temperature and to examine expression of PLA2 in E. coli at different inducer concentrations for commercialization. This is to produce PLA2 enzyme in E. coli which fulfilled the Halal concept in Islamic religion. There were five clone of E. coli used in this study. Three of the clones harboring Pla2 gene. Meanwhile, another two clones act as negative and positive control respectively. 100 uL overnight cultured was transferred into new bottle containing LB broth. After two hours, the cultures were supplemented with arabinose at two different concentrations which were 0.02% and 0.2% to induce the expression of the desired protein. Samples that have been collected were run through SDS-PAGE electrophoresis. Concurrently positive and negative control strains which do not contain plasmid and plasmid without Pla2 gene were also run. Results gained indicates that only induced samples showed expression of PLA2 protein which were pBAD Thio - TOPO Pla2 (-TAG 5) and pBAD Thio - TOPO Pla2 (-TAG 8) either in 0.02% or 0.2% concentrations of arabinose. pBAD Thio-TOPO Pla2 (-TAG 16) is believed to be mutated. It also shows positive correlation between the growth rate and the amount of protein produced. However, significant effect towards the amount of protein being expressed was also found to be given by the incubation temperature. Result shows that incubation temperature of 37°C produced higher protein amount when compared to incubation temperature of 27°C.